1996
DOI: 10.1021/jm960531r
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Biological Evaluation, Calcium Channel Antagonist Activity, and Anticonvulsant Activity of Felodipine Coupled to a Dihydropyridine−Pyridinium Salt Redox Chemical Delivery System

Abstract: 3-(2-Hydroxyethyl) 5-methyl 1,4-dihydro-2,6-dimethyl-4-(2,3-dichlorophenyl)-3,5-pyridinedi-carboxyla te (7) was prepared using a modified Hantzsch reaction, which was then elaborated to 3-[2-[[(1-methyl-1,4-dihydropyrid-3-yl)carbonyl]oxy]ethyl]5-methyl 1,4-dihydro-2,6-dimethyl-4-(2,3-dichlorophenyl)-3,5-pyridinedicarboxylat e [10, felodipine-chemical delivery system (CDS)]. The equipotent 3-(2-hydroxyethyl) 7 (IC50 = 3.04 x 10(-8) M) and felodipine-CDS (10, IC50 = 3.10 x 10(-8) M) were, respectively, 2- and 21… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

1999
1999
2015
2015

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 26 publications
0
17
0
Order By: Relevance
“…Brain drug delivery approaches are available [113, 114]. One such approach, using a chemical delivery system (CDS), has already been applied to increase brain concentrations of the widely used DHP felodipine [115]. Bodor’s lipophilic [(1-methyl-1,4-dihydropyrid-3-yl)-carbonyl]oxy (amino) acts as a chemical delivery system that, after entry into brain is oxidized to a polar pyridinium species.…”
Section: Ltcc Drugsmentioning
confidence: 99%
“…Brain drug delivery approaches are available [113, 114]. One such approach, using a chemical delivery system (CDS), has already been applied to increase brain concentrations of the widely used DHP felodipine [115]. Bodor’s lipophilic [(1-methyl-1,4-dihydropyrid-3-yl)-carbonyl]oxy (amino) acts as a chemical delivery system that, after entry into brain is oxidized to a polar pyridinium species.…”
Section: Ltcc Drugsmentioning
confidence: 99%
“…The antiseizure potency of a CDS for felodipidine (72) was studied by Yiu and Knaus. 248 In vitro investigations revealed that, while the parent drug is very stable in biological media, biotransformations of the CDS (73, Fig. 29) showed a pseudo-®rst-order kinetics with t 1/2 of 15.5 h in rat plasma and 1.3 h in 20% rat brain homogenate.…”
Section: Anticonvulsantsmentioning
confidence: 99%
“…Accordingly, coupling this CDS to a γ-aminobutyric acid derivative (GABA-CDS, 3) [8] , or diphenylhydantoin (DPH-CDS, 4) [9] , resulted in superior anticonvulsant protection in animal seizure models compared to the parent compounds GABA or DPH. In an earlier study, it was shown that the C-3 2-hydroxyethyl analog of felodipine (5) and the felodipine-CDS (6) provided protection against maximal electroshock (MES) induced seizures in mice but were inactive in the subcutaneous metrazol (scMet) anticonvulsant screen [10] . The felodipine-CDS (6) enters the brain readily, and it undergoes facile oxidation to a pyridinium species that is retained in brain tissues up to four days after drug administration.…”
Section: Introductionmentioning
confidence: 99%
“…The felodipine-CDS (6) enters the brain readily, and it undergoes facile oxidation to a pyridinium species that is retained in brain tissues up to four days after drug administration. However, the slow hydrolysis rate of the pyridinium ester to the 3-(2-hydroxyethyl) compound 5 and the rapid egression of felodipine-CDS (6) from brain likely contributed to the modest anticonvulsant activity exhibited by the felodpine-CDS (6) [10] . The long acting second-generation CCA amlodipine (7), having a novel C-2 -CH2OCH2CH2NH2 substituent, is a potent antihypertensive drug that is amenable to once-a-day dosing [11] .…”
Section: Introductionmentioning
confidence: 99%